Climate Change Adaptation through Urban Agriculture Food Barn in Tambakrejo, Semarang City - Sholeh, Muh; Naryatmojo, Deby Luriawati; Putro, Saptono; Simbolon, Andri Sumihar (Jurnal Abdimas, 2024)
As a metropolitan city with limited land for food production, Semarang faces a challenge in maintaining its food security. This issue is exacerbated by climate change, increasing the risk of crop failure. As a result, Semarang still relies on food supplies from other regions. This situation has encouraged innovation through the concept of urban farming. Urban farming allows communities to optimize vacant land, providing a mitigation strategy against food shortages while creating green open spaces and offering economic value. The urban farming activities are supported by SAKA Energi Muriah Limited and Semarang State University, which conduct community empowerment, including: (1) socialization, (2) formation of farmer groups, (3) training for farmer groups, (4) urban farming system training, (5) urban farming implementation, (6) provision of facilities and technology, and (7) monitoring and evaluation. The results show that urban farming successfully provides an alternative food source, especially during floods, and increases community awareness of food security and the environment. Training in cultivation techniques, organizational development, and provision of facilities and infrastructure have been key factors in the program's success. The urban farming model applied includes vertical pipes, hanging pots, and polybags. The plants to be cultivated include Brazilian spinach, celery, strawberries, medicinal plants, and ornamental plants. Active community involvement through institution-building, training, and implementation has strengthened residents' ability to utilize limited urban land while contributing to the provision of green open spaces.